An Analysis of Language in University Students' Text Messages. Issue 3 (1st April 2014) - Lyddy, Fiona; Farina, Francesca; Hanney, James; Farrell, Lynn; Kelly O'Neill, Niamh
Abstract: Concerns over effects of 'textisms' on literacy have been reinforced by research identifying processing costs associated with reading textisms. But to what extent do such studies reflect actual textism use? This study examined the textual characteristics of 936 text messages in English (13391 words). Message length, nonstandard spelling, sender and message characteristics and word frequency were analyzed. The data showed that 25% of word content used nonstandard spelling, the most frequently occurring category involving omission of capital letters. Types of nonstandard spelling varied only slightly depending on the purpose of the text message, while the overall proportion of nonstandard spelling did not differ significantly. Less than 0.2% of content was 'semantically unrecoverable.' Implications for experimental studies of textisms are discussed.